Bioactive Peptides in Greek Goat Colostrum: Relevance to Human Metabolism - Maria Louiza Petre; Anna Nefeli Kontouli Pertesi; Olympia Eirini Boulioglou; Eleana Sarantidi; Artemis G. Korovesi; Athina Kozei; Angeliki I. Katsafadou; George T. Tsangaris; Antonia Trichopoulou; Athanasios K. Anagnostopoulos (Foods)
Colostrum is essential for the survival and development of newborn mammals. This primary source of nourishment during the first days of infant life is rich in functional components conductive to the enhancement of neonate immunity and growth. Compared with mature milk, a higher protein and peptide content is observed in colostrum, whilst it is low in fat and carbohydrates. The functional properties of colostrum are closely linked to the release of bioactive peptides during the gastrointestinal digestion of colostrum proteins. Our study aimed to comprehensively analyze the whey proteome of colostrum from indigenous Greek goats and to examine the influence of bioactive peptides released during digestion on human metabolism. Colostrum and mature milk samples from healthy ewes were subjected to nanoLC-MS/MS analysis, revealing differentially expressed proteins. These proteins were functionally characterized and subjected to in silico digestion. Using machine learning models, we classified the peptide functional groups, while molecular docking assessed the binding affinity of the proposed angiotensin-converting enzyme (ACE)- and dipeptidyl peptidase IV (DPPIV)-inhibitory peptides to their target molecules. A total of 898 proteins were identified in colostrum, 40 of which were overexpressed compared with mature milk. The enzymatic cleavage of upregulated proteins by key gastrointestinal tract proteases and the downstream analysis of peptide sequences identified 117 peptides predicted (with >80% confidence) to impact metabolism, primarily through modulation of the renin–angiotensin system, insulin secretion, and redox pathways. This work advances our understanding of dietary bioactive peptides and their relevance to human metabolism, highlighting the potential health benefits of colostrum consumption.